Gut microbiota imbalances in Tunisian participants with type 1 and type 2 diabetes mellitus. Issue 6 (18th June 2019) - Fassatoui, Meriem; Lopez-Siles, Mireia; Díaz-Rizzolo, Diana A.; Jmel, Haifa; Naouali, Chokri; Abdessalem, Ghaith; Chikhaoui, Asma; Nadal, Belén; Jamoussi, Henda; Abid, Abdelmajid; Gomis, Ramon; Abdelhak, Sonia; et al.
Abstract : Gut microbiota plays an important role in the regulation of the immune system and host's metabolism. We aimed to characterize the gut microbiota of Tunisian participants with and without diabetes. We enrolled ten participants with type 1 diabetes mellitus (T1DM), ten patients with type 2 diabetes mellitus (T2DM), and 11 subjects without diabetes. Bacteria was quantified in fecal samples by quantitative PCR (qPCR). Statistical tests and multivariate analysis were performed using RStudio program. Results showed that the proportions of Firmicutes, Akkermansia muciniphila, and Faecalibacterium prausnitzii ( P ≤0.041), as well as, the ratio Firmicutes/Bacteroidetes decreased in participants with T1DM compared with those without diabetes (p = 0.036). Participants with T2DM presented a reduction in the amounts of A. muciniphila and F. prausnitzii compared with those without diabetes ( P ≤0.036). Furthermore, A muciniphila is negatively correlated with glucose level ( P =0.022) and glycated hemoglobin (HbA1c) ( P =0.035). Multivariate analysis revealed that participants with diabetes formed a cluster apart compared with those without diabetes. In conclusion the gut bacteria of Tunisian participants with diabetes was altered. The gut bacterial profile, especially the distribution of A muciniphila in participants with diabetes was affected by glycemic dysregulation. The investigation of the gut microbiota may help clinicians to improve diagnosis and treatment of diabetes and its complications.